2020
DOI: 10.33596/coll.71
|View full text |Cite
|
Sign up to set email alerts
|

Power Sharing, Capacity Building, and Evolving Roles in ELSI: The Center for the Ethics of Indigenous Genomic Research

Abstract: Persistent, unresolved issues stemming from a legacy of scientific exploitation and bio-colonialism have kept many tribal nations from participating in genomic research. The Center for the Ethics of Indigenous Genomic Research (CEIGR) aims to model meaningful community engagement that moves toward more inclusive and equitable research practices related to genomics. This article reflects on key successes and challenges behind CEIGR's efforts to shape Ethical, Legal and Social Implications (ELSI) research in way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Both reviews and workshop discussions emphasised the importance of adapting research practices to the needs of different groups and designing accessible communication strategies that ensure critical information is conveyed clearly and effectively (Kobayashi et al, 2013 ; Campbell et al, 2017 ; Kraft and Doerr, 2018 ; Sabatello et al, 2019 ; Hendricks-Sturrup and Johnson-Glover, 2021 ; Uebergang et al, 2021 ; Garofalo et al, 2022 ). Such communication strategies were thought to improve the trustworthiness of research (Blanchard et al, 2020 ). However, it was also reported that critical information on genomic health research is sometimes communicated in ways that can cause confusion and misunderstandings for participants, posing barriers for participation in genomic research (Garofalo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both reviews and workshop discussions emphasised the importance of adapting research practices to the needs of different groups and designing accessible communication strategies that ensure critical information is conveyed clearly and effectively (Kobayashi et al, 2013 ; Campbell et al, 2017 ; Kraft and Doerr, 2018 ; Sabatello et al, 2019 ; Hendricks-Sturrup and Johnson-Glover, 2021 ; Uebergang et al, 2021 ; Garofalo et al, 2022 ). Such communication strategies were thought to improve the trustworthiness of research (Blanchard et al, 2020 ). However, it was also reported that critical information on genomic health research is sometimes communicated in ways that can cause confusion and misunderstandings for participants, posing barriers for participation in genomic research (Garofalo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies in both reviews advocated community engagement throughout research processes (Boyer et al, 2011 ; Chadwick et al, 2014 ; Beans et al, 2019 ; Tsosie et al, 2019 ; Blanchard et al 2020 ; Hiratsuka et al, 2020 ; Hudson et al, 2020 Kaladharan et al, 2021 ), and some incorporated it in the design, development and implementation of their studies (Hiratsuka et al, 2012 ). The rapid review touched upon the lessons learnt from research initiatives that aspired to prioritise co-production.…”
Section: Resultsmentioning
confidence: 99%
“…This work is based on a collaboration between two research consortia: (1) the Northwest-Alaska Pharmacogenomics Network (NWA-PGRN), a collaboration of researchers from Oregon Health & Science University, Southcentral Foundation, the University of Montana, and the University of Washington and tribal communities in Alaska and Montana partnered to address pharmacogenomic and precision medicine research with AIAN populations [10][11][12][13]45]; and (2) the University of Oklahoma's Center for the Ethics of Indigenous Genomic Research (CEIGR), a university and community partnership Center of Excellence in Ethical, Legal, and Social Implications Research that formed to support AIAN communities to determine how to best approach genomic research [46,47]. The NWA-PGRN and CEIGR investigators have expertise in anthropology, bioethics, epigenetics, genetics, pharmacology, and public health and collaborate with six AIAN communities across the USA on genomic research projects addressing communityidentified health priorities related to genomic and precision medicine research.…”
Section: Methodsmentioning
confidence: 99%
“…Despite a growing trend of engaging other historically marginalized communities in the conduct of research that may affect them, in genomics, there have been relatively few endeavors to specifically engage LGBTQI+ individuals in research priority setting, research design, and the dissemination of research results. 75 , 76 , 77 , 78 , 79 , 80 While LGBTQI+ individuals may also identify as members of other historically marginalized groups, outreach efforts to these other groups do not typically address the impact of sex or gender on their attitudes to genomic research. This omission is especially problematic in the context of studies that have examined genetic correlates of gender and sex characteristics with little regard for the group harms that may result from their findings.…”
Section: A Chain Of Conflation: How Inaccurate Data Collection and Re...mentioning
confidence: 99%